(untitled) (Fiep Bulletin - online, 2015)
This study aimed to know the characteristics of individuals participating in the Cultural Centre, and evaluating the results regarding the practice of classical ballet in the maintenance of functional autonomy. The study was carried out between June-September 2013 were selected eight subjects aged 60 years or more, practicing classic ballet once a week. All subjects signed a consent form Escla¬recido that ensures anonymity and the possibility of withdrawal. For data collection we used an adaptation of the Senior Assessment System Autonomy of Action (SysSen), applying only the senior physical activity questionnaire (QSAP) on three dimensions: (a) what the individual does; (b) what the individual should do; (c) what the individual wants to do, plus five open questions concerning the practice of classical ballet. The QSAP allows representative set of personal needs regarding previously selected aspects of physical fitness indices. The data contained in the application forms were entered and tabulated in Microsoft Office Excel 2007 program after the period of 120 days was applied to the test again, seeking positive change. The results showed that 71% had improved balance and memory. As for autonomy 89% of the subjects returned to perform activities such as cleaning the floor, squatting, lifting and climbing stairs. Still, the data showed us that feelings of opportunity, personal fulfillment, overcoming have been provided through the practice of classical ballet.